Pengembangan dan Pemberdayaan UMKM Serta Pelatihan Pembuatan Kripik Gedebog Pisang Aneka Rasa Desa Mudung, Kepohbaru, Bojonegoro - Sugito (Community: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mudung Village is a lowland area in kepohbaru district, Bojonegoro regency. The majority of the population work as farmers, apart from growing rice and tobacco, many banana trees are planted next to house and in rice dields but the fruit is only used for sale. In Mudung Villange, quite a lot of people are enterpreneurs as MSME producers and also as grocery store traders. One of the assets in Mudung Villange, which is rearely used, is the gedebog banana stem. This is a tree that contains lots of nutrients ranging from vitamin A, B and C which are good for the body, and there is a need for outreach to MSME so that they are more skilled in product marketing. The method used in this assistance is AsedBased Community Development (ABCD). Which is to build public awareness to be aware of the assets owned by the community itself. It is important to active social change by raising awareness of the community itself by knowning their assets. In the asset-bassed or ABCD approach, several strategies are used, including:discovery, dream, design, devine, destiny. The result of the strategy used in this research is the growing awareness of the people of Mudung hamlet regarding the banana tree assets they own, and apart from that, the community is also starting to utilize and process banana gedebog into processed products such as banana gedebog chips, namely various flavours of banana gedebog chips and know how to use them. Marketing a good product